A STUDY OF THE ENGLISH TEXTBOOKS FOR SENIOR HIGH SCHOOL IN FOUR ENGLISH SKILLS ON GENDER EQUALITY IN SERANG CITY - BANTEN - Gailea, Nurhaedah; Rasyid, Yumna (PPs UNJ, 2015)
The objective of the research is to find out deeply the aspects of equal gender on English textbooks for Senior High School by Indonesian and English writer in Serang City. The method used in this research is qualitative research with content analysis technique.The data collected through document review. The research finding shows that the perecentage of men are higher than women in the aspects of main character and historical event, the use of equal language, public and domestic role, and art talent, sport, and intellectual competence on the books of indonesia writer in four language skills such as listening, speaking, reading, and writing.This description shows that women are inferior because of culture, misinterpretation of religion, and patriarchy system factor. Whreas the perecentage of men and women are gender equal on the book of English writer, especially in the main character, the language equal, the public and domestic role, and the art talent, but the sport and intelectual competence showed that the perencentage of men are high. It means that women have opportunity as men and especially domestic role is responsibility of both men and women. It can be concluded that the Englsh textbook is written by Indonesian that called curriculum 2013 can not be used as English lesson, whereas the English textbook of English writer can recommend as English lesson because it found the equal gender.